Hubungan Disiplin Belajar Dengan Prestasi Siswa Dalam Pembelajaran Pendidikan Agama Kristen Kelas XI SMK Negeri 1 Sigumpar Dusun Dolok Nabolon Porsea - Erni Desi Hasibuan; Damayanti Nababan; Malani Simanungkalit; Betty AS Pakpahan; Rawatri Sitanggang (Journal of Creative Student Research, 2023)
As is known, students' active learning will grow and be visible if the classroom conditions are enjoyable for them. Furthermore, the class atmosphere will be pleasant if students are active in class. Students' active learning in class can be stimulated through the use of appropriate teaching strategies by teachers. One strategy that is appropriate to use is the Discovery Learning learning strategy, which is a strategy that involves students playing an active role in learning by training students to think critically through problem solving by formulating hypotheses, searching for information, analyzing, and arriving at conclusions. Through this strategy, the problem of students often not doing assignments, and others will be resolved. The research method used in writing this journal is the library study method, namely by collecting some information through books, journals, magazines, newspapers, and also through other sources that are relevant to the title of this journal. Keywords: active learning of students, Discovery Learning Strategy.